Instituto Católico de Estudos Superiores: a formação da intelectualidade brasileira católica (1910 1932) - Fagundes, Paula Martins Xavier (2014)
The present work is a historical research and aimed to investigate the importance and the role of Catholic leaders involved in the establishment of the Catholic Institute of Higher Studies (CIHS). Founded in 1932 in the city of Rio de Janeiro, the CIHS was the first step taken for the foundation of the future Pontifical Catholic University of Rio de Janeiro, founded in 1941 and recognized in 1946 as papal. The chronological cut taken by the research was the period of 1910 to 1932, because it was the period of a more intense action of the Catholic church in social, political, cultural and religious context. Moreover, the formation of a network of Catholic intellectuals allowed discussions regarding the establishment of a Catholic university to take place within the economic and social elites, allowing the foundation of the CIHS. The study was based on analysis of newspaper articles published at the time, as well as in the analysis of Revista A Ordem, published by D. Vital Center, an agency of the high Catholic hierarchy. Newspapers do Brasil and A Noite were fundamental to check the movement of the Catholic elite in order to establish the CIHS. Based on the results we can say that there was the conformation of an intellectuals network linked to the Catholic Church, in the period from 1910 to 1932, linking projects to get into the sphere of the Brazilian higher education, giving a first step towards such project when founded the Catholic Institute of Higher Studies in 1932